Efectividad de la orientación emprendedora: El papel del capital social y las capacidades - Job Rodrigo-Alarcón; Gloria Parra-Requena; Pedro Manuel García-Villaverde (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2014)
– In last years entrepreneurial orientation has generated an increased interest in the field of entrepreneurship. The literature review allows us to suggest the need to analyze the ambiguity and complexity of the relationship between entrepreneurial orientation and firms' performance. In this work, we study this relationship from a configurational approach, addressing the consistency of relational and organizational aspects with entrepreneurial orientation. The aim of this work is to develop a configurational model to explain how the conjunction between social capital and internal capabilities can foster the relationship between entrepreneurial orientation and performance. We propose three theoretical models - universal, contingent and configurational - which are defined by theoretical propositions. Also, we explore and exemplify empirically these relationships through a case study of Spanish agri-food industry. Finally, we draw a series of conclusions from the proposed models and we propose future lines of research.
Keywords: M13; L12; 330; Entrepreneurial orientation; social capital; Technological capabilities; Marketing capabilities; Theoretical model